2007
DOI: 10.1063/1.2723867
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and ferroelectric engineering of vapor-transport-equilibrated, near-stoichiometric lithium tantalate for frequency conversion

Abstract: Near-stoichiometric lithium tantalate ͑SLT͒ crystals were produced from congruent lithium tantalate by vapor transport equilibration, and several important optical and ferroelectric properties were measured. The effect of vapor transport conditions and surface preparation on reproducible ferroelectric engineering of SLT has been studied. Control of these effects along with dramatic decreases in the sensitivity to photorefractive damage and 532 nm absorption has allowed near-room-temperature generation of 10 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…The annealing of congruent lithium tantalate (CLT) wafers with prereacted Li-rich powder of 70% LiO 2 and 30% Ta 2 O 5 during 100 h at 1100 C was used during VTE process. 34 In our experiments, we used two different types of electrodes: (1) liquid electrodes based on saturated aqueous solution of LiCl; (2) solid state metal electrodes (100-nm-thick Ni) or conductive transparent oxide (200-nm-thick In 2 O 3 :Sn (ITO)) deposited by DC ion plasma sputtering. The circular solid state electrodes (2-3 mm in diameter) of the same material were deposited on both polar surfaces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annealing of congruent lithium tantalate (CLT) wafers with prereacted Li-rich powder of 70% LiO 2 and 30% Ta 2 O 5 during 100 h at 1100 C was used during VTE process. 34 In our experiments, we used two different types of electrodes: (1) liquid electrodes based on saturated aqueous solution of LiCl; (2) solid state metal electrodes (100-nm-thick Ni) or conductive transparent oxide (200-nm-thick In 2 O 3 :Sn (ITO)) deposited by DC ion plasma sputtering. The circular solid state electrodes (2-3 mm in diameter) of the same material were deposited on both polar surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] It belongs to the family of lithium niobate (LN) and lithium tantalate (LT) crystals, which are the most popular nonlinear-optical ferroelectric materials. 36 This uniaxial ferroelectric demonstrates the lowest coercive field within all representatives of LN and LT family (about 200 times lower than in CLN).…”
Section: Model Of the Fatigue Process Caused By Growth Of The Fromentioning
confidence: 99%
“…13 Such improved optical and ferroelectric properties make VTE-LT crystals very promising for production of nonlinear optical devices with tailored domain structure. 14 The polarization reversal process was studied in VTE-LT crystals by integral methods only. 12,14 The activation-type field dependence of the switching time was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…14 The polarization reversal process was studied in VTE-LT crystals by integral methods only. 12,14 The activation-type field dependence of the switching time was revealed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] However, it is known that the lower defect density, and consequently less pinning sites, in conjunction with the reduced coercive field of this material, may cause unstable domain structures. 8 In fact, it has been observed that even moderate heat treatment can lead to domain backswitching in NSLT. 9 The standard technique to study domain structures for periodically poled ferroelectrics is by using domain-selective etchants, mostly based on hydrofluoric acid (HF).…”
Section: Introductionmentioning
confidence: 99%